Improving Students' Speaking Skills through English Movie - Umitnana, Maria Radegunda; Pale, Erlinda Sonya; Bouk, Edmundus (Universitas Nurul Jadid, 2024)
The Speaking is a complex language skill that involves not only articulating words and sentences but also expanding and expressing ideas meaningfully. This study investigates how using Disney's